The Dual Role of Surfactant Protein-D in Vascular Inflammation and Development of Cardiovascular Disease - Colmorten, Kimmie B.; Nexoe, Anders Bathum; Sorensen, Grith L. (Frontiers in Immunology, 2019)
Cardiovascular disease (CVD) is responsible for 31% of all global deaths. Atherosclerosis is the major cause of cardiovascular disease and is a chronic inflammatory disorder in the arteries. Atherosclerosis is characterized by the accumulation of cholesterol, extracellular matrix, and immune cells in the vascular wall. Recently, the collectin surfactant protein-D (SP-D), an important regulator of the pulmonary immune response, was found to be expressed in the vasculature. Several in vitro studies have examined the role of SP-D in the vascular inflammation leading to atherosclerosis. These studies show that SP-D plays a dual role in the development of atherosclerosis. In general, SP-D shows anti-inflammatory properties and dampens local inflammation in the vessel, as well as systemic inflammation. However, SP-D can also exert a pro-inflammatory role, as it stimulates C-C chemokine receptor 2 inflammatory blood monocytes to secrete tumor necrosis-factor α and increases secretion of interferon-γ from natural killer cells. In vivo studies examining the role of SP-D in the development of atherosclerosis agree that SP-D plays a proatherogenic role, with SP-D knockout mice having smaller atherosclerotic plaque areas, which might be caused by a decreased systemic inflammation. Clinical studies examining the association between SP-D and cardiovascular disease have reported a positive association between circulatory SP-D level, carotid intima-media thickness, and coronary artery calcification. Other studies have found that circulatory SP-D is correlated with increased risk of both total and cardiovascular disease mortality. Both in vitro, in vivo, and clinical studies examining the relationship between SP-D and CVDs will be discussed in this review.